THE MAIN IDEAS OF THE FOUNDER OF THE GERMAN SCHOOL OF PHILOSOPHY - Muradov, Sanjar Aslonovich (Innovative Development in Educational Activities, 2023)
This article analyzes the ethical views of Immanuel Kant. Immanue Kant is the founder of German classical philosophy and his views on morality and morality have a special place in human development.